Correction: Payo et al. Geometrical Analysis of the Inland Topography to Assess the Likely Response of Wave-Dominated Coastline to Sea Level: Application to Great Britain. J. Mar. Sci. Eng. 2020, 8, 866 - Andres Payo; Chris Williams; Rowan Vernon; Andrew G. Hulbert; Kathryn A. Lee; Jonathan R. Lee (Journal of Marine Science and Engineering, 2022)
There was an error in the original publication [...]